2008
DOI: 10.1089/end.2007.0299
|View full text |Cite
|
Sign up to set email alerts
|

Holmium Laser Lithotripsy for Ureteral Calculi: Predictive Factors for Complications and Success

Abstract: Surgeon experience is a predictive factor for complications and success for ureteroscopic holmium laser lithotripsy for ureteric calculi. Experienced surgeons have fewer complications, and the success rate is higher. Sex, stone location, size, and age were not significantly related to complication or success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 17 publications
8
53
1
4
Order By: Relevance
“…The edematous and inflamated mucosa surronding and partly covering the stone or fibroepithelial polyp results impede visualization of the stone and make it difficult to perform the lithotripsy. 10,11 The increment of irrigation fluid pressure to obtain a clear image may result in stone migration into the renal collecting system.…”
Section: Discussionmentioning
confidence: 99%
“…The edematous and inflamated mucosa surronding and partly covering the stone or fibroepithelial polyp results impede visualization of the stone and make it difficult to perform the lithotripsy. 10,11 The increment of irrigation fluid pressure to obtain a clear image may result in stone migration into the renal collecting system.…”
Section: Discussionmentioning
confidence: 99%
“…Grade 4a [20] comparing surgical outcomes between experts and trainees, the surgical outcome in terms of stone-free rate and complication rate was superior in the supervised trainees group than in the least experienced expert group. In another series, Netsch et al [21] evaluated the impact of surgical experience on the outcome of ureteroscopy done for a single upper ureteric stone and found that the supervised trainees had a similar overall outcome to their mentor consultants.…”
Section: Grade 3bmentioning
confidence: 93%
“…Accumulated literature data have well demonstrated that the as the stone gets buried into the ureteric wall, this condition (often being called as "impaction") may affect not only the spontaneous passage rates; but also the ultimate success as well as procedure related complications of endourological stone removal methods [1,[12][13][14][15][16].…”
Section: Assessment Of Ureteral Stone Impaction Into the Ureteric Wallmentioning
confidence: 99%